Assessment of histology's performance compared with PCR in the diagnosis of Helicobacter pylori infection - Manel Moalla; Lassaad Chtourou; Basma Mnif; Slim Charfi; Hend Smaoui; Mon Boudabous; Leila Mnif; Ali Amouri; Hela Gdoura; Adnene Hammami; Tahya Boudawara; Nabil Tahri (Future Science OA)
Aim: Histology is the most widely used test to detect H. pylori. PCR is less used but allows the detection of both infection and antibiotics' resistance. Methods: We conducted a monocentric cross-sectional study, collecting 97 symptomatic patients to assess the diagnostic performance of histology in the detection of H. pylori infection compared with PCR. Results: Sensitivity of histology in comparison with PCR was 81.5% and specificity was 56.3%. A history of anti-H. pylori therapy intake, as well as the density of the bacterium on the gastric sample and the presence of gastric atrophy, were significantly correlated to the PCR's result in terms of H. pylori detection. Conclusion: Thus, histology can be considered as an efficient test compared with PCR in H. pylori detection.